Education Innovation for Hypertension Prevention: Pocketbook and Video-Based Learning Using Local Foods - Rosiana Eva Rayanti; Theresia Destin Natalia; Wilda Pascalia Noya; Catherine Natawirarindry; Indriani Bastian Christy Wauran; Oliviani Yanto; Galuh Ambar Sasi; Dwi Laksono (Universitas Nurul Jadid, 2026)
Hypertension is a major health problem among older adults because it increases the risk of chronic disease complications. In Ngrawan Village, 70 older adults were identified as having hypertension during activities at the elderly integrated health post (Posyandu Lansia), while 87.14% of the foods consumed by older adults were classified as high in salt. This condition highlights the need to strengthen the role of community health cadres in promoting hypertension-preventive behaviors in the community. This community service program aimed to enhance the capacity of Posyandu cadres to provide hypertension prevention education based on local food resources. The activity was conducted using a service-learning approach involving 25 health cadres in Ngrawan Village, Central Java, on September 15, 2024. The educational media used included a pocketbook entitled Ngadi Salira Atasi Hipertensi and a DASH diet video entitled Diet Ingkang Atasi Saben Hipertensi, which were developed using local language, attractive visuals, and examples of local foods. Evaluation was carried out using a questionnaire assessing language clarity, visual presentation, and overall media quality. The results showed that all cadres (100%) received the media very positively. This positive reception was followed by increased readiness among cadres to deliver education in a more active, communicative, and contextual manner, as well as to encourage the adoption of healthy behaviors among older adults, particularly reducing salt intake, choosing healthier local foods, and monitoring blood pressure regularly.